Results of a study of soybean source material for breeding purposes under the conditions of Primorsky Territory - E. A. Vasina; E. S. Butovets; L. M. Lukyanchuk (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. A study of the soybean gene pool adapted to the conditions of Primorsky Territory in search of useful agronomic traits is essential for further use in breeding programs.Materials and methods. Soybean accessions from the germplasm collection were tested in 2019–2021 at the Federal Scientific Center of Agricultural Biotechnology of the Far East named after A.K. Chaika. The study included 213 accessions of various origin. Cv. ‘Primorskaya 4’ served as the reference. An objective assessment of the potential of the said research material was made.Results. Three years of experiments resulted in selecting promising soybean genotypes with a set of important agronomic traits for breeding programs. Compared to the reference ‘Primorskaya 4’, an increase of more than 35% in productivity was observed in the cultivars ‘Mestnaya’ (Russia), ‘Jilin’ (China), ‘Montreal’ (France), and ‘XP 977-1.9’ (USA). Cvs. ‘No. 075-2’ (USA), ‘K0152’ (Ukraine), ‘Muzanze Stamm M 4789/74’, ‘SOJA 1065’ and ‘Adsoi’ (Germany) were characterized by earliness (100 days). Cvs. ‘Mestnaya’ and ‘HS Atlas’ may be interesting for breeders due to their highest oil content: 25.9% and 26.0%, respectively. The highest protein content was found in cvs. ‘Zhuravushka’ (39.2%), ‘XN 4’ (41.9%), ‘Torlitsa’ (41.9%) and ‘XP 977-1.9’ (39.5%). Cvs. ‘Pi 6D 4182’, ‘XN 4’, ‘Skelya’ and ‘HS Atlas’ manifested resistance to Septoria brown spot. The results of the assessment for adaptability potential showed that the following cultivars of different origin had the highest resistance to environmental stresses: ‘Primorskaya 4’ (–2.5), ‘Torlitsa’ (–2.0) and ‘Kassidi’ (–3.0).